Corrosion and Wear Resistance of Micro‐Arc Oxidation Composite Coatings on Magnesium Alloy AZ31—The Influence of Inclusions of Carbon Spheres. Issue 9 (8th August 2019) - Li, Chang-Yang; Feng, Xiao-Lei; Fan, Xiao-Li; Yu, Xiao-Tong; Yin, Zheng-Zheng; Kannan, M. Bobby; Chen, Xiao-Bo; Guan, Shao-Kang; Zhang, Jun; Zeng, Rong-Chang
Abstract : Poor corrosion and wear resistance of magnesium (Mg) alloys restrict their applications. Herein, corrosion and wear‐resistant films are formed upon Mg alloy AZ31 through a micro‐arc oxidation (MAO) process in silicate electrolyte in the presence of carbon spheres (CS). Surface morphology, chemical composition, corrosion resistance, hardness, and coefficient of friction (CoF) of the MAO coatings are investigated using field‐emission scanning electron microscopy (FE‐SEM), Fourier transform infrared spectrometry (FTIR), X‐ray diffractometer (XRD), X‐ray photoelectron spectroscopy (XPS), electrochemical and hydrogen evolution measurements, automatic micro‐hardness testing, and reciprocating tribometer, respectively. Results demonstrate that the surface morphology and hardness of MAO coatings vary with the concentration of CS. The presence of CS results in an increased coating thickness from 8.0 ± 1.8 to 12.2 ± 1.8 μm, mean pore size from 0.7 ± 0.1 to 1.9 ± 0.1 μm, open porosity of MAO coating from 4.2 ± 0.4 to 5.6% ± 1.1%, and coating hardness from 347.0 ± 59.0 to 853.0 ± 67.3 Vickers‐hardness (HV). Furthermore, CS‐modified MAO coatings lead to improved corrosion resistance in comparison with that of the neat MAO counterparts. Moreover, the high hardness and formation of SiC of CS‐modified coatings lead to a low and stabilized CoF, which implies an enhanced wear resistance. Abstract : Solid carbon spheres as additives in silicate electrolyte, reacting with SiO2 generated during micro‐arc oxidation (MAO) or plasma electrolyte oxidation process, result in the formation of ceramic‐phase SiC. As a result, solid carbon sphere‐modified MAO coating is fabricated with a higher coating thickness, surface hardness, and lower corrosion current density as well as a lower coefficient of friction.